2008
DOI: 10.1097/tp.0b013e31817ef190
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Consequences of Delayed Graft Function in Deceased Donor Renal Transplant Patients Receiving Antithymocyte Globulin Induction

Abstract: In kidney transplantation with routine rATG induction, DGF was related to size and gender, donor creatinine, and immunosuppressive protocol. Despite low first-year rejection rates, DGF was associated with inferior patient survival. Importantly, patients with DGF continued to be at risk for rejection beyond the first year. Donor and recipient selection impacts short-term outcomes, and induction alone may not confer a long-term advantage without further modification of baseline therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 41 publications
2
40
2
2
Order By: Relevance
“…A systematic review and meta-analysis by Yarlagadda et al 10 combined the results of eight studies that included patient survival as an outcome of interest and found no significant increase in the risk for mortality for patients with DGF. A recent report by Patel et al 11 (published after the period covered by the meta-analysis) revealed that DGF was associated with an increased risk for 12-mo mortality but no difference in death-censored graft failure among high-risk KTR who underwent induction therapy with anti-thymocyte globulin; however, none of the aforementioned studies explicitly evaluated DWGF as an outcome of interest.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis by Yarlagadda et al 10 combined the results of eight studies that included patient survival as an outcome of interest and found no significant increase in the risk for mortality for patients with DGF. A recent report by Patel et al 11 (published after the period covered by the meta-analysis) revealed that DGF was associated with an increased risk for 12-mo mortality but no difference in death-censored graft failure among high-risk KTR who underwent induction therapy with anti-thymocyte globulin; however, none of the aforementioned studies explicitly evaluated DWGF as an outcome of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Patel et al [59] demonstrated that a high BMI (>30), sirolimus-based regimen, female to male donation and donor creatinine >1.5 mg/dl are independent risk factors for DGF. The patients with DGF had a worse survival compared to non-DGF group at 1 year.…”
Section: Role Of Thymoglobulin In Prevention Of Delayed Graft Functiomentioning
confidence: 99%
“…Overall, the vast majority of kidney transplants are performed using kidneys from standard criteria donors with moderate DGF rates of 21-31% (7)(8)(9). (10,11).…”
Section: Despite Achieving 1-and 5-year Survival Approaching 90 and 6mentioning
confidence: 99%